The Lesson Study as a training strategy for learning to teach in college. Some reflections derived from an Educational Innovation Project developed at the National University of Education (UNAE) - del Río Fernández, José Luis (Revista Complutense de Educación, 2021)
This article presents some reflections derived from an Educational Innovation Project developed at the National University of Education (Ecuador), entitled "The Improvement of University Teaching through Collaborative Action-Research and Lesson Study”. Along two academic courses, a group of teachers decided to work as a team in the design, implementation, observation and assessment of a series of class sessions that served as the basis for the analysis of teaching provided. During this process, the strategies and tools to gather information were the non-participating observation, the checklist and the videographic record. The subsequent triangulation of the data obtained and the group discussion allowed us to discover and identify the strengths and the weaknesses found in its development. The results obtained show that, thanks to the dialogue and shared reflection, the teachers that made up the work team had the possibility of modifying or reinterpreting certain behavior patterns that were considered common in the classroom. In addition, new ways of approaching teaching in certain subjects emerged. To close the paper, some ideas and discussion elements are raised that invite us to continue the debate on pedagogical training for the necessary development of university teaching.